The role of word-categories in trait-taxonomy: evidence from the Dutch personality taxonomy - Dick P.H. Barelds; Boele De Raad (International Journal of Personality Psychology, 2015)
We examined how the use of personality descriptive terms from word categories other than adjectives affect the factor structure. Use was made of the previously published (2008) Dutch trait structure comprising eight factors: (versions of) the Big Five factors, and three new factors, labeled Virtue, Competence, and Hedonism. This 2008 structure lends itself well to study the role of word categories, because it adopted an unrestricted approach in selection of trait-descriptors and included words from different word categories. Some differences were found between the eight factors in terms of the contribution from different word categories, but the meaning of the three new factors appeared to be determined mostly by trait adjectives. When analyzing the 953 typical adjectives only (N = 1,466), an eight factor solution was found that closely resembled the structure of the whole dataset, whereas analyzing a subset of 441 adjectives that had been used in the previous Dutch lexical study supported the Big Five. Additional analyses on an old dataset containing 1,203 adjectives (N = 400) yielded an eight factor structure that was highly similar to the new Dutch lexical structure. Together these results suggest that particularly the inclusion of a larger number of trait terms is responsible for finding the 2008 Dutch lexical structure.